Corrosion and wear behaviors of boronized AISI 316L stainless steel - Kayalı, Yusuf; Büyüksağiş, Aysel; Yalçın, Yılmaz (Springer, 2013)
In this study, the effects of a boronizing treatment on the corrosion and wear behaviors of AISI 316L austenitic stainless steel (AISI 316L) were examined. The corrosion behavior of the boronized samples was studied via electrochemical methods in a simulation body fluid (SBF) and the wear behavior was examined using the ball-on-disk wear method. It was observed that the boride layer that formed on the AISI 316L surface had a flat and smooth morphology. Furthermore, X-ray diffraction analyses show that the boride layer contained FeB, Fe2B, CrB, Cr2B, NiB, and Ni2B phases. Boride layer thickness increased with an increasing boronizing temperature and time. The boronizing treatment also increased the surface hardness of the AISI 316L. Although there was no positive effect of the coating on the corrosion resistance in the SBF medium. Furthermore, a decrease in the friction coefficient was recorded for the boronized AISI 316L. As the boronizing temperature increased, the wear rate decreased in both dry and wet mediums. As a result, the boronizing treatment contributed positively to the wear resistance by increasing the surface hardness and by decreasing the friction coefficient of the AISI 316L.
Keywords: AISI 316L SS; Corrosion; Wear; Scanning Electron Microscopy; SEM; Surface Modification